(untitled) (Archaeologia Adriatica, 2010)
The archaeological excavations in the very nucleus of the city of Varaždin resulted in numerous and diverse material bearing witness to the manner of existence, trade, customs, and the lifestyle standards of citizens from the 15th to the 19th centuries. The medieval glass, distinguished from several hundred glass finds, comes from various sites in the city. These consists primarily of fragments, while only two bottles were complete, and one beaker was missing the upper section. Glass vessels of various forms and purposes can be assigned according to the typological characteristics to several groups: biconical flasks, bottle of the kuttrolf type, conical smooth beakers and conical optically blown beakers, krautstrunk type beakers, and footed goblets. A special group is composed of window glass, represented by oculi, while for one object the function has not yet been determined. The analysis and dating of the glass from Varaždin are based on typological features and comparisons with similar finds from other contexts, since generally speaking the products of the European workshops cannot be distinguished in terms of form and purpose, rather the quality of the glass and manner of execution are recognizable for given production centers. The stratigraphic position of some of the finds was important for their dating, and hence the krautstrunk beaker found at the vase of the defensive ditch of the castle (Stari Grad) was dated to the 15th century on the basis of the other finds from the stratum. The medieval glass from Varaždin belongs to the period from the beginning of the 15th to the second half of the 16th centuries, and according to the color, the quality of the glass, and its workmanship, its origin can be sought in the glass workshops of Venice (biconical flasks, conical beakers, footed goblets), Budapest (biconical flasks, oculi), and the German forest glassworks (kuttrolf bottles, krautstrunk beakers). It is also possible that high quality products made "a façon de Venise" could have been manufactured in some central European glass production centers.